치면열구전색 전후의 어린이 소변 내 Bisphenol-A의 농도 변화 - 신아라; Ah Ra Shin; 김지혜; Ji-hye Kim; 전은숙; Eun Suk Jeon; 정윤숙; Yun-sook Jung; 송근배; Keun-bae Song; 최연희; Youn-hee Choi (대한구강보건학회지, 2017)
Objectives: The objectives of this study were to investigate the changes in bisphenol A (BPA) concentrations in urine from before to after sealant filling and the relationship between BPA and the number of teeth with sealed surfaces. Methods: Thirty-one children aged 6 and 7 years from three elementary schools in Daegu city who did not have any sealant and resin filling were selected as subjects. Urine samples were collected before and after sealant filling until 24 hours, with informed consent from their caregivers. The BPA concentration in all the collected urine samples was analyzed at Seegene Medical. Statistical analysis was performed using the Friedman test, Scheirer-Ray-Hope test, and the repeated-measures generalized linear mixed model of SPSS version 22.0. Results: The BPA concentrations increased from 3.49-mg/g creatinine before to 4.91-mg/g creatinine 2-3 hours later and to 4.15-mg/g creatinine after 24 hours. The more teeth with sealed surfaces, the higher the BPA concentration in children, but the difference was not statistically significant (P>0.05). Conclusions: The BPA concentrations were highest at 2-3 hours after sealant filling and decreased at 24 hours. Exposure to the sealant appears to have a meaningful correlation with the concentration of BPA in the urine of children.